Dry heating affects the multi-structures, physicochemical properties, and in vitro digestibility of blue highland barley starch - Liu, Shuang; Liu, Hang; Gao, Shanshan; Guo, Shang; Zhang, Cheng (Frontiers in Nutrition, 2023)
As a physical method for starch modification, dry heating treatment (DHT) at high temperatures (150 ℃ and 180 ℃, respectively) was applied to blue highland barley (BH) starch with different duration (2 h and 4 h). The effects on its multi-structures, physicochemical properties and in vitro digestibility were investigated. The results showed that DHT had changed the morphology of BH starch, and the diffraction pattern remained ‘A’-type crystalline structure. However, with extension of DHT temperature and time, the amylose content, gelatinization temperature, enthalpy value, swelling power and pasting viscosity of modified starches decreased, while the light transmittance, solubility, water and oil absorption capacities increased. Additionally, compared to native starch, the content of rapidly digestible starch in modified samples increased after DHT, whereas those of slowly digestible starch and RS decreased. On the basis of these results, the conclusion could be drawn that DHT is an effective and green way to transform multi-structures, physicochemical properties and in vitro digestibility of BH starch. These fundamental information might be meaningful to enrich the theoretical basis of physical modification on BH starch, and extend the applications of BH in food industry.